Distortion of metal-ceramic fixed partial dentures resulting from metal-conditioning firing - (:unkn) unknown (My University, 1996)
The aim of this study was to investigate the distortion of metal-ceramic prostheses that occurs during metal-conditioning firing and to examine whether the distortion might be controlled by embedding the castings in an investment bulk and applying a prior heat treatment. The distortion of palladium-copper and nickel-chromium frameworks was evaluated by means of inner fit and horizontal linear measurements of the framework length. There was no statistically significant difference between palladium-copper and nickel-chromium frame-works in the changes in inner fit. In addition, there was no statistically significant difference between the invested test group and the control group in changes in fit. However, the mean deformation in framework length recorded for invested palladium-copper frameworks (-20.20 microns) was significantly smaller than that recorded for control palladium-copper frameworks (52.20 microns).
Keywords: Analysis of Variance; Chromium Alloys; Copper; Dental Casting Technique; Palladium; Surface Properties; Oxidation-Reduction; Denture, Partial, Fixed; Denture Design; Metal Ceramic Alloys; Dental Casting Investment